1981
DOI: 10.1007/bf00230187
|View full text |Cite
|
Sign up to set email alerts
|

Superpotency and superaffinity phenomena in the stimulation of steroidogenesis in adrenocortical cells by adrenocorticotropin-tobacco mosaic virus conjugates

Abstract: Adrenocorticotropin-(1-24)-tetracosapeptide was covalently attached to tobacco mosaic virus in two different manners: (i) through a handle near the C-terminus on tyrosine-(23) and (ii) through a handle at the N-terminus on serine-(1). Compounds of type (i) with their N-terminal message sequence freely exposed on the virion surface were considerably more potent for stimulating steroidogenesis in isolated adrenocortical cells than those of type (ii) with a more congested message. Conjugates with 50 or less hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…Pretreatment The present results are in complete agreement with our earlier results on fluorescence labeling of these cells using a water-soluble class of fluorescent melanotropic macromolecular reagents (6, 7) as well as with those of Schwyzer and coworkers, who developed conjugates of MSH with tobacco mosaic virus (8)(9)(10)(11)(12). Using the melanotropin fluorescein conjugate, we demonstrated that both melanotic as well as amelanotic human melanoma cells expressed membrane melanocortin receptors (6,7).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Pretreatment The present results are in complete agreement with our earlier results on fluorescence labeling of these cells using a water-soluble class of fluorescent melanotropic macromolecular reagents (6, 7) as well as with those of Schwyzer and coworkers, who developed conjugates of MSH with tobacco mosaic virus (8)(9)(10)(11)(12). Using the melanotropin fluorescein conjugate, we demonstrated that both melanotic as well as amelanotic human melanoma cells expressed membrane melanocortin receptors (6,7).…”
Section: Discussionsupporting
confidence: 92%
“…In this respect, these results are similar to electron microscopic visualization of internalized receptor-ligand complex for a glucagon-serum albumin preparation labeled with 17 nanometer gold particles (23). These results are consistent with those obtained earlier using fluorescent tobacco mosaic virus-MSH conjugates (8)(9)(10)(11)(12) and fluorescent polyvinyl alcohol-MSH conjugates (6, 7).…”
Section: Synthesis Of Peptide-conjugated Beadssupporting
confidence: 91%
See 3 more Smart Citations